Spin state engineered ZnxCo3-xO4 as an efficient oxygen evolution electrocatalyst - Ramsundar, Rani Mohan; Pillai, Vijayamohanan Kunjukrishna; Joy, Pattayil Alias (Physical Chemistry Chemuical Physics, 2018)
Oxygen evolution is the key step in the oxidation of water in electrolyzers and photoelectrochemical cells for the production of hydrogen. Developing a non-precious metal oxide catalyst with good electrocatalytic activity for the oxygen evolution reaction (OER) is very challenging. In this work, nanostructured ZnxCo3-xO4 has been shown as an efficient catalyst with a low overpotential for the OER in 0.1 M KOH solution. Substitution of Co2+ in the spinel oxide Co3O4 with Zn2+ creates a higher number of high-spin Co3+, which is found to be directly correlated with the OER activity of ZnxCo3-xO4. Zn0.8Co2.2O4 (x = 0.8) with the optimum amount of Co2+/Co3+ and high-spin Co3+ content showed a very low overpotential of approximate to 250 mV, at 10 mA cm(-2), with a turnover frequency of approximate to 3 x 10(-3) s(-1) for the OER. The high Faradaic efficiency along with the stability of Zn0.8Co2.2O4 and electrocatalytic activity comparable with that of precious metal oxides indicate that this composition is a promising catalyst for water oxidation.